Emotion Knowledge, Theory of Mind, and Language in Young Children: Testing a Comprehensive Conceptual Model - Conte, Elisabetta; Ornaghi, Veronica; Grazzani, Ilaria; Pepe, Alessandro; Cavioni, Valeria (Frontiers in Psychology, 2019)
Numerous studies suggest that both emotion knowledge and language abilities are powerfully related to young children’s theory of mind. Nonetheless, the magnitude and direction of the associations between language, emotion knowledge, and theory-of-mind performance in the first years of life are still debated. Hence, the aim of this study was to assess the direct effects of emotion knowledge and language on theory-of-mind scores in 2- and 3-year-old children. A sample of 139 children, aged between 24 and 47 months (M = 35.5 months; SD = 6.73), were directly administered measures of emotion knowledge, theory of mind, and language. We conducted structural equation modeling (SEM) to evaluate the effects of these variables within a single comprehensive framework, while also controlling for any effects of age and gender. The proposed structural equation model provided an excellent fit for the data, indicating that both children’s emotion knowledge and their language ability had direct positive effects on theory of mind scores. In addition, age was found to wield statistically significant effects on all the variables under study, whereas gender was not significantly associated with any of them. These findings suggest the importance of fostering young children’s emotion knowledge and language with a view to enhancing their comprehension of mental states.